Discrete-event simulation of truck–excavator systems in surface mining using a finite-source closed-loop queuing model - Danang Setiawan; Haswika Haswika; Qurtubi Qurtubi; M. Zikra Zizo Alfieta (Universitas Serang Raya, 2025)
Truck-excavator interaction in surface mining is often modeled as finite-source, closed-loop queuing systems. An optimization-based approach is typically used, assuming deterministic and homogeneous fleet configurations. This paper aims to contribute to the current literature by implementing a simulation-based approach, discrete-event simulation (DES), to analyze a finite-source closed-loop queuing model in a surface mining operation. The case study used was coal overburden removal activities, which operate under a first-come, first-served discipline, and loop through four phases: loading, hauling, dumping, and returning. Under the current fleet configuration, the overburden removal activity is experiencing a 19,17% production shortfall and a match factor (MF) of 0.74. An MF below 1 indicates an under-truck system, where the excavator often idles while waiting for the trucks to arrive. Three scenarios were tested using the validated DES model: (1) the as-is scenario with four trucks and one excavator, (2) variations of truck quantity, and (3) a route improvement scenario to reduce travel time. Simulation results indicate that adding five trucks yields the highest productivity (533.86 BCM/hour), utilization (92.48%), and MF (0.91), while the route improvement scenario achieved nearly comparable performance (513.94 BCM/hour, 88.86% utilization, MF = 0.88) with lower resource. Although the current case study operates under a homogeneous fleet with a single excavator, this study also tests the DES model under heterogeneous fleet configurations and a multi-server setup involving two excavators. These findings highlight the DES capability in modeling and analyzing a queuing system under a finite-source closed-loop, both for homogeneous and heterogeneous fleet configurations.